Late Cretaceous eclogitic high-pressure relics in the Bitlis Massif - Oberhänsli, R.; Koralay, E.; Candan, O.; Pourteau, Amaury; Bousquet, R. (2013)
A new occurrence of eclogites was found in the Kesandere valley in the eastern most part of the Bitlis complex, SE Anatolia. These high-pressure (HP) relics were preserved in calc-arenitic metasediments within the high-grade metamorphic basement of the Bitlis complex. The eclogitic parageneses were strongly overprinted during decompression and heating. These new eclogites locality complements the evidence of blueschist-facies metamorphism documented recently in the meta-sedimentary cover sequence of this part of the Bitlis complex. Thermodynamic calculations suggest peak conditions of ca. 480-540 °C/1.9-2.4 GPa. New U/Pb dates of 84.4 ±.9 and 82.4 ±.9 Ma were obtained on zircons from two Kesandere eclogite samples. On the basis of geochemical criteria, these dates are interpreted to represent zircon crystallization during the eclogitic peak stage. Kesandere eclogites differ from those previously described in the western Bitlis complex (Mt. Gablor locality) in terms of lithologic association, protolithic origin, and peak P-T conditions (600-650°C/1.0-2.0 GPa, respectively). On the other hand, eclogitic metamorphism of Kesandere metasediments occurred shortly before blueschist-facies metamorphism of the sedimentary cover (79-74 Ma 40Ar/39Ar white mica). Therefore, the exhumation of Kesandere eclogites started between ca. 82 and 79 Ma, while the meta-sedimentary cover was being buried. During this short time span, Kesandere eclogite were likely uplifted from ~65 to 35 km depth, indicating a syn-subduction exhumation rate of ~4.3 mm/a. Subsequently, eclogite-and blueschist-facies rocks were likely retrogressed contemporarily during collision-type metamorphism (around 72-69 Ma). The Bitlis HP rocks thus sample a subduction zone that separated the Bitlis-Pütürge (Bistun?) block from the South-Armenian block, further north. To the south, Eocene metasediments of the Urse formation are imbricated below the Bitlis complex. They contain (post Eocene) blueschists, testifying separation from the Arabian plate and southward migration of the subduction zone. The HT overprint of Kesandere eclogites can be related to the asthenospheric flow provoked by subducting slab retreat or break off. © 2014 Taylor & Francis.